CORRELATION BETWEEN THE INDICATORS BMI, WHR AND LEVEL OF PHYSICAL ACTIVITY WITH CORONARY RISK IN INTERSTATE BUS DRIVERS OF A COMPANY OF ROAD TRANSPORT RONDÔNIA (Fiep Bulletin - online, 2015)
Aiming to analyze and correlate with body composition, level of physical activity with the risk of coronary interstate bus drivers, the sample group consisted of 106 drivers (age 38.3 ± 8.5 years). The analytical plan and used the correlation BioEstat 5.0 by applying the Pearson equation. The results showed that drivers had a mean and standard deviation (SD) with a profile (BMI) for overweight (26.1 ± 3,9kg / m2), of these, 44.3% were overweight and 14.1% obese, and abdominal fat (WHR) in high-risk level (0.93 ± 0.07), although 29.2% were at high risk, very high risk 21.7% and 88.6% of motorists are at risk moderate to very high. Regarding the pattern of physical activity (IPAQ), 20.7% were sedentary, 38.6% are irregularly active B, 14.1% are irregularly active A, 25.4% active and less than 1% very active. The results also show no correlation to coronary risk factors between BMI and WHR variables, with values of r = 0.391 and p =
Keywords: Body Composition; physical activity; coronary risk.